2016
DOI: 10.1016/j.chom.2016.04.002
|View full text |Cite|
|
Sign up to set email alerts
|

Posttranscriptional m 6 A Editing of HIV-1 mRNAs Enhances Viral Gene Expression

Abstract: Summary Covalent addition of a methyl group to the adenosine N6 (m6A) is an evolutionarily conserved and common RNA modification that is thought to modulate several aspects of RNA metabolism. While the presence of multiple m6A editing sites on diverse viral RNAs was reported starting almost 40 years ago, how m6A editing affects virus replication has remained unclear. Here, we used photo-crosslinking-assisted m6A sequencing techniques to precisely map several m6A editing sites on the HIV-1 genome and report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
487
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 324 publications
(529 citation statements)
references
References 38 publications
(56 reference statements)
34
487
8
Order By: Relevance
“…The integrated function of YTHDFs is further exemplified by recent studies on how the m 6 A modification on HIV RNA affects viral gene expression. Overexpression of any of the YTHDFs resulted in a similar effect of promotion of protein synthesis from HIV RNAs, and inhibition of HIV-1 virus infection by decreasing HIV-1 reverse transcription [35,36].…”
Section: Discussionmentioning
confidence: 94%
“…The integrated function of YTHDFs is further exemplified by recent studies on how the m 6 A modification on HIV RNA affects viral gene expression. Overexpression of any of the YTHDFs resulted in a similar effect of promotion of protein synthesis from HIV RNAs, and inhibition of HIV-1 virus infection by decreasing HIV-1 reverse transcription [35,36].…”
Section: Discussionmentioning
confidence: 94%
“…Of these, by far the most prevalent internal modified base found on mRNAs is m 6 A, and recent work has now begun to reveal how m 6 A affects mRNA function and how to precisely map the m 6 A residues present on mRNAs (1)(2)(3). m 6 A is also highly prevalent on a wide range of different viral RNA species (4)(5)(6)(7)(8)(9)(10)(11)(12)(13), and recently, the first reports demonstrating a significant phenotypic effect of these m 6 A modifications have been published (10)(11)(12)(13)(14). Therefore, we will focus this review entirely on m 6 A and how this particular modification might affect different aspects of the viral life cycle.…”
mentioning
confidence: 99%
“…The sequence specificity of the writer proteins that add m 6 A to mRNAs is not entirely clear, though it has been known for some time that the minimal sequence context is 5=-Rm 6 AC-3= (where R is a purine) (6). A larger consensus sequence, 5=-RRm 6 ACH-3= (where H is A, C, or U), has also been suggested (2,3,35), and evidence indicates that 5=-Gm 6 AC-3= is generally preferred over 5=-Am 6 AC-3= (6,10). Yet, at most 10% of the consensus m 6 A sites found on mRNAs are actually modified and, despite the random distribution of consensus target sites, m 6 A residues are also, for currently unclear reasons, concentrated in the 3= untranslated region (UTR) of cellular mRNAs (36,37).…”
mentioning
confidence: 99%
“…In the third study, however, the opposite effect was observed with respect to the YTHDF proteins, HIV-1 mRNA expression, and viral replication. 49 The specific m 6 A sites reported in the three studies also differ, perhaps reflecting different cell lines and viral clones used in each study. Ongoing work will clarify the effect of RNA modifications on HIV-1 and explore their effects other viruses.…”
Section: Viral Infectionmentioning
confidence: 99%
“…[49][50][51] Though each study took different approaches and reaches different conclusions in some cases, they do converge in many respects. They find that HIV-1 RNA carries multiple m 6 A peaks that appear to be important in infection, and that the cellular host responds with infection-specific methylation of multiple transcripts potentially involved in the response to viral infection.…”
Section: Viral Infectionmentioning
confidence: 99%